Diabetes up-regulated collagen IV and laminin Î±5 genes in mRNA and protein levels in seminiferous tubules of C57BL/6 adult mice - Khordad, Elnaz; Nikravesh, Mohammad Reza; Jalali, Mehdi; Fazel, Ali Reza; Sankian, Mojtaba; Alipour, Fatemeh (Cellular and Molecular Biology, 2020)
Diabetes is a disease associated with impairment of the male reproductive system that causes complications such as decreased testosterone, the diameter of the seminiferous tubule, libido, and fertility. Extracellular matrix (ECM) molecules are involved in testicular development and spermatogenesis. Laminin and collagen are key proteins in seminiferous tubule basement membrane and play an important role in spermatogenesis. The present study was conducted to investigate the effect of diabetes on collagen IV and laminin Î±5 changes in mice testis. In this experimental study, 40 mice (C57BL/6) were divided randomly into 4 groups: 1) Control group: without intervention, 2) Diabetic group: treated mice with 50 mg/kg streptozotocin (STZ), 3) Diabetic + Insulin group: treated mice with STZ and insulin, and 4) Sham group: received citrate buffer. After 35 days, the left testes of all specimens were used for Real-Time PCR while their right testes were applied for immunohistochemical study and Periodic acid–Schiff (PAS) staining. This study showed that gene expression and immunoreactivity of laminin Î±5 and collagen IV were significantly increased in diabetic mice compared to other groups (P<0.05). Also, PAS staining showed the thickness of seminiferous tubule basement membrane in the Diabetic group compared to other group increased significantly (p<0.05). In Diabetic + Insulin compared to Diabetic group, gene expression, the intensity of immunoreactivity and thickness of seminiferous tubule basement membrane decreased significantly (P<0.05). Our findings indicated that diabetes causes up-regulation of collagen IV and laminin Î±5 in mRNA and protein levels in the seminiferous tubule basement membrane and may cause disorder in spermatogenesis in mice.